Pain intensity control in virtual reality via modulated cooling rates in thermal grill illusion - Hori, Shinnosuke; Liu, Renke; Igarashi, Haruo; Sawada, Hideyuki (Frontiers in Virtual Reality, 2025)
As virtual reality (VR) technology advances, the need for realistic pain presentation to enhance immersion grows. The thermal grill illusion (TGI), which elicits a burning sensation through the simultaneous application of warm and cold stimuli, has emerged as a promising technique. To apply TGI in VR for pain intensity control, clarifying the relationship between stimulus parameters and perceptual intensity is crucial. In this study, we constructed a TGI display using six thermoelectric devices and conducted two user experiments. The first experiment investigated the relationship between the cooling rate of cold stimuli and TGI-induced pain intensity. Results indicated that faster cooling rates intensified perceived pain. The second experiment implemented pain intensity control in a VR environment. As a result, six out of seven participants reported that the perceived intensity of pain changed in response to the changes in the VR stimuli. Our findings demonstrate that manipulating the cooling rate can effectively control pain intensity in VR, enhancing the realism and immersion of VR experiences.